Diagnosis and Management of Choledochal Cyst in Adult : An Experience in a Tertiary Level Hospital in China - Kaiser, ABM; Barua, Subrata; Biswas, Siddartha; Nahar, Nur; Mohammad, Noor; Ara, Shamim; Wei, Niu; Liang, Benjia; Niu, Jun (Journal of Chittagong Medical College Teachers’ Association, 2016)
The cystic dilatation of the biliary tract is a rare disease and uncertain origin. It is recognized more frequently in children; however, its incidence comes increasing in adults, representing 20% of the cases. The aims of this study to demonstrate our experience with choledochal cyst and to evaluate morbimortality rates, discuss the aetiopathogenesis, presentation, management, and outcome with review of the literature. A retrospective study and review of the records of all the patients above 15 years, who underwent therapeutic intervention of choledochal cyst in Qillu Hospital of Jinan, China, was carried out. Ten cases of choledochal cyst were found, 8 female, with mean age 31 years. These included 8 cases of Todani type I and one case each of type II and type III. The predominant symptoms were abdominal pain and jaundice. Abdominal mass and past history of cholangitis and pancreatitis were seen in 2 patients. Investigations included ultrasound in 8 patients, CT in 7, ERCP in 3, and MRCP in 5. Surgical intervention included complete excision of the cyst with hepaticojejunostomy and cholecystectomy (Type I) excision of the diverticulum (Type II) and ERCP sphincterotomy (Type III). Malignancy was not seen in any patients. The long-term postoperative complications included cholangitis in two patients. Biliary tract cystic dilatation is a rare disease. However, its incidence is increasing in the adult population; so, it must be thought as differential diagnosis when facing obstructive jaundice. JCMCTA 2015 ; 26 (2) : 67 - 72